SASCI-Mayo Clinic Fellows webinar: Lifelong management of adults with repaired tetralogy of Fallot - Weich, H; Engelbrecht, A; Khan, S; Anderson, J; Barsness, GW; Holmes, DR (SA Heart Journal, 2026)
This is the second in our series of South African Society of Cardiovascular Intervention (SASCI)-Mayo Clinic summit webinars to be published. This webinar was hosted by the regular faculty, with Dr Anderson, a congenital heart disease expert from the Mayo Clinic, in attendance. He provides background on the lifetime management of repaired tetralogy of Fallot (rToF), followed by a clinical case (presented by Dr Engelbrecht) spanning 3 distinct phases in the patient’s lifetime. The discussants are cardiology fellows from South African universities. Objective: This manuscript, arising from the webinar series, summarises a multidisciplinary discussion on the lifelong management of rToF. Design: Edited transcript of an expert webinar jointly hosted by SASCI and the Mayo Clinic faculty. Case: The management of a female patient is discussed in three stages at different age points of the patient’s lifetime. The patient received a surgical rToF as a 1-year-old girl. She was then followed longitudinally into adulthood. At 19 years old, she was asymptomatic at presentation with severe pulmonary regurgitation (PR), progressive right ventricle (RV) remodelling, and borderline functional capacity. The discussion explored thresholds for intervention, imaging strategies where cardiac magnetic resonance imaging (CMR) access is limited, and surgical versus transcatheter valve replacement options. The patient ultimately underwent surgical pulmonary valve replacement (PVR) with a 27 mm bioprosthetic valve. At phase 3, she presented at the age of 29 with degeneration of her bioprosthetic valve. She was evaluated and received a transcatheter valve. Key messages: (1) Understanding embryology and surgical history informs lifelong surveillance; (2) PRdriven RV remodelling is central to management; (3) objective imaging and functional markers (RV volumes, QRS, cardiopulmonary exercise test [CPET], arrhythmia burden) guide timing more reliably than symptoms alone; (4) procedural choice balances anatomy, concomitant lesions, device availability, and lifetime reintervention planning; and (5) lifelong exercise and structured follow-up are essential. Online resource: Recorded SASCI fellows webinars (restricted to verified healthcare professionals) are available from: https://www.sasci.co.za/content/page/sasci-educational-videos1.